Analisis Miskonsepsi Siswa pada Materi Stoikiometri Menggunakan Test Diagnostic Essay Berbantuan CRI - Nurhamidah; Wiwit; Delta Novita Sari (ALOTROP, 2024)
This research is a quantitative descriptive study which aims to determine students' misconceptions about stoichiometry material using a diagnostic essay test instrument assisted by the Certainty Of Response Index (CRI) at SMA Negeri 9 Bengkulu City. The field trial sample included 24 students of class X MIPA 1 and an implementation sample of 27 students of class The results of the empirical validation test obtained 17 fit questions and 2 misfit questions from the 19 questions tested. The results of the differential power test showed that 19 items tested were included in the good differential power category with logit standard error (SE) values for 19 items < 0.5. The research results showed that overall student misconceptions were 25% in the low category. The highest misconception lies in the concept of determining product mass, with a misconception percentage of 52%, which is in the medium category. Keywords: misconceptions, test diagnostic essay, stoichiometry.